위아전절제술 후 발생한 근위부 비장동맥 가성동맥류 - 정헌(Hun Jung); 최성희(Seong Hee Choi); 신숙희(Suk Hee Shin); 안지영(Ji Yeong An); 최민규(Min Gew Choi); 노재형(Jae Hyung Noh); 손태성(Tae Sung Sohn); 배재문(Jae-Moon Bae); 김성(Sung Kim) (Annals of surgical treatment and research, 2009)
Splenic artery pseudoaneurysm (SAP) is a very rare case, postoperatively. SAP originates from many causes such as complication of chronic pancreatitis in adults and blunt abdominal trauma in children. SAP related to surgery may result from direct tissue injury during operation. Urgent angiography is helpful in diagnoses and life-saving procedures as the endovascular embolization simultaneously. However, endovascular management is not a definite treatment modality in patients previously operated on because the blood supply of remaining organs will be insufficient after embolization. In this paper, we report a rare case that is proximal splenic artery pseudoaneurysm after radical subtotal gastrectomy in a 63-year-old male patient with early gastric cancer, as well as a brief review. Splenic artery pseudoaneurysm (SAP) is a very rare case, postoperatively. SAP originates from many causes such as complication of chronic pancreatitis in adults and blunt abdominal trauma in children. SAP related to surgery may result from direct tissue injury during operation. Urgent angiography is helpful in diagnoses and life-saving procedures as the endovascular embolization simultaneously. However, endovascular management is not a definite treatment modality in patients previously operated on because the blood supply of remaining organs will be insufficient after embolization. In this paper, we report a rare case that is proximal splenic artery pseudoaneurysm after radical subtotal gastrectomy in a 63-year-old male patient with early gastric cancer, as well as a brief review. KCI Citation Count: 0